International news. Bulletin of the Provisional International Contact Commision. . Internation news
Ook op omslag : Internation news Continues: The Marxist. Theoretical organ ... (ZK 6097). French ed.: Nouvelles internationaux. Organe de la Commission internationale de contact (ZDK 6651).